Fabrication of carbon nanospheres by the pyrolysis of polyacrylonitrile–poly(methyl methacrylate) core–shell composite nanoparticles - Wei, Dafu; Zhang, Youwei; Fu, Jinping (Beilstein Journal of Nanotechnology, 2017)
Carbon nanospheres with a high Brunauer–Emmett–Teller (BET) specific surface area were fabricated via the pyrolysis of polyacrylonitrile–poly(methyl methacrylate) (PAN–PMMA) core–shell nanoparticles. Firstly, PAN–PMMA nanoparticles at high concentration and low surfactant content were controllably synthesized by a two-stage azobisisobutyronitrile (AIBN)-initiated semicontinuous emulsion polymerization. The carbon nanospheres were obtained after the PAN core domain was converted into carbon and the PMMA shell was sacrificed via the subsequent heat treatment steps. The thickness of the PMMA shell can be easily adjusted by changing the feeding volume ratio (FVR) of methyl methacrylate (MMA) to acrylonitrile (AN). At an FVR of 1.6, the coarse PAN cores were completely buried in the PMMA shells, and the surface of the obtained PAN–PMMA nanoparticles became smooth. The thick PMMA shell can inhibit the adhesion between carbon nanospheres caused by cyclization reactions during heat treatment. The carbon nanospheres with a diameter of 35–65 nm and a high BET specific surface area of 612.8 m2/g were obtained from the PAN–PMMA nanoparticles synthesized at an FVR of 1.6. The carbon nanospheres exhibited a large adsorption capacity of 190.0 mg/g for methylene blue, thus making them excellent adsorbents for the removal of organic pollutants from water.
Keywords: carbon nanospheres; core–shell nanoparticles; emulsion polymerization; polyacrylonitrile

(untitled) - Schadler, L. S.; Giannaris, S. C.; Ajayan, P. M. (Appl. Phys. Lett., 1999)

(untitled) - Zubizarreta, L.; Arenillas, A.; Pis, J. J. (Int. J. Hydrogen Energy, 2009)

(untitled) - Flandrois, S.; Simon, B. (Carbon, 1999)

(untitled) - Lou, X. W.; Li, C. M.; Archer, L. A. (Adv. Mater., 2009)

(untitled) - Huo, K. F.; An, W. L.; Fu, J. J.; Gao, B.; Wang, L.; Peng, X.; Cheng, G. J.; Chu, P. K. (J. Power Sources, 2016)

(untitled) - Liu, Y. C.; Qiu, X. P.; Huang, Y. Q.; Zhu, W. T. (Carbon, 2002)

(untitled) - Panomsuwan, G.; Saito, N.; Ishizaki, T. (Carbon, 2016)

(untitled) - Tashima, D.; Yamamoto, E.; Kai, N.; Fujikawa, D.; Sakai, G.; Otsubo, M.; Kijima, T. (Carbon, 2011)

(untitled) - Lu, W.; Liu, M.; Miao, L.; Zhu, D.; Wang, X.; Duan, H.; Wang, Z.; Li, L.; Xu, Z.; Gan, L. (Electrochim. Acta, 2016)

(untitled) - Auer, E.; Freund, A.; Pietsch, J.; Tacke, T. (Appl. Catal., A, 1998)

(untitled) - Han, J.-S.; Chung, D. Y.; Ha, D.-G.; Kim, J.-H.; Choi, K.; Sung, Y.-E.; Kang, S.-H. (Carbon, 2016)

(untitled) - Arayachukeat, S.; Palaga, T.; Wanichwecharungrugang, S. P. (ACS Appl. Mater. Interfaces, 2012)

(untitled) - Huang, X.; Wu, S.; Du, X. (Carbon, 2016)

(untitled) - Song, X.; Gunawan, P.; Jiang, R.; Leong, S. S. J.; Wang, K.; Xu, R. (J. Hazard. Mater., 2011)

(untitled) - Chen, A.; Li, Y.; Yu, Y.; Li, Y.; Xia, K.; Wang, Y.; Li, Y.; Li, S. (Carbon, 2016)

(untitled) - Qiao, W. M.; Song, Y.; Lim, S. Y.; Hong, S. H.; Yoon, S. H.; Mochida, I.; Imaka, T. (Carbon, 2006)

(untitled) - Chen, G. X.; Hong, M. H.; He, Q.; Chen, W. Z.; Elim, H. I.; Ji, W.; Chong, T. C. (Appl. Phys. A: Mater. Sci. Process., 2004)

(untitled) - Pol, V. G.; Pol, S. V.; Moreno, J. M. C.; Gedanken, A. (Carbon, 2006)

(untitled) - Sun, X.; Li, Y. (Angew. Chem., Int. Ed., 2004)

(untitled) - Yoon, S. B.; Sohn, K.; Kim, J. Y.; Shin, C.-H.; Yu, J.-S.; Hyeon, T. (Adv. Mater., 2002)

(untitled) - Herring, A. M.; McKinnon, J. T.; McCloskey, B. D.; Filley, J.; Gneshin, K. W.; Pavelka, R. A.; Kleebe, H.-J.; Aldrich, D. J. (J. Am. Chem. Soc., 2003)

(untitled) - Ding, L.; Olesik, S. V. (Nano Lett., 2004)

(untitled) - Kim, B. J.; Changs, J. Y. (Macromolecules, 2006)

(untitled) - Fujikawa, D.; Uota, M.; Sakai, G.; Kijima, T. (Carbon, 2007)

(untitled) - Dong, Y.-R.; Nishiyama, N.; Egashira, Y.; Ueyama, K. (Ind. Eng. Chem. Res., 2008)

(untitled) - Li, Y.; Chen, J.; Xu, Q.; He, L.; Chen, Z. (J. Phys. Chem. C, 2009)

(untitled) - White, R. J.; Tauer, K.; Antonietti, M.; Titirici, M.-M. (J. Am. Chem. Soc., 2010)

(untitled) - Einert, M.; Wessel, C.; Badaczewski, F.; Leichtwei, T.; Eufinger, C.; Janek, J.; Yuan, J.; Antonietti, M.; Smarsly, B. M. (Macromol. Chem. Phys., 2015)

(untitled) - Schäfer, C. G.; Vowinkel, S.; Hellmann, G. P.; Herdt, T.; Contiu, C.; Schneider, J. J.; Gallei, M. (J. Mater. Chem. C, 2014)

(untitled) - Vowinkel, S.; Schäfer, C. G.; Cherkashinin, G.; Fasel, C.; Roth, F.; Liu, N.; Dietz, C.; Ionescu, E.; Gallei, M. (J. Mater. Chem. C, 2016)

(untitled) - Tang, C.; Qi, K.; Wooley, K. L.; Matyjaszewski, K.; Kowalewski, T. (Angew. Chem., Int. Ed., 2004)

(untitled) - Aqil, A.; Detrembleur, C.; Gilbert, B.; Jérôme, R.; Jérôme, C. (Chem. Mater., 2007)

(untitled) - Yang, L. C.; Shi, Y.; Gao, Q. S.; Wang, B.; Wu, Y. P.; Tang, Y. (Carbon, 2008)

(untitled) - Yang, G.-z.; Xu, R.-s.; Chen, M.; Wang, X.; Ling, L.-c.; Zhang, R.; Yang, J.-h. (New Carbon Mater., 2008)

(untitled) - Yang, G. Z.; Yang, J. H.; Liu, Y.; Jia, R. P.; Xu, R. S.; Wang, X.; Ling, L. C. (Coal Convers., 2009)

(untitled) - Lu, A.-H.; Sun, T.; Li, W.-C.; Sun, Q.; Hun, F.; Liu, D.-H.; Guo, Y. (Angew. Chem., Int. Ed., 2011)

(untitled) - Lei, Z.; Zhao, M.; Dang, L.; An, L.; Lu, M.; Lo, A.-Y.; Yu, N.; Liu, S.-B. (J. Mater. Chem., 2009)

(untitled) - Wang, Y.; Su, F.; Wood, C. D.; Lee, J. Y.; Zhao, X. S. (Ind. Eng. Chem. Res., 2008)

(untitled) - Zhang, Y.; Zhuang, X.; Gu, W.; Zhao, J. (Eur. Polym. J., 2015)

(untitled) - Wang, Y.; Dong, L.; Xiong, R.; Hu, A. (J. Mater. Chem. C, 2013)

(untitled) - Zhang, Y.; He, Y.; Zhao, J. (Eur. Polym. J., 2014)

(untitled) - Boguslavsky, L.; Baruch, S.; Margel, S. (J. Colloid Interface Sci., 2005)

(untitled) - Landfester, K.; Antonietti, M. (Macromol. Rapid Commun., 2000)

(untitled) - Zhang, Y.; Jiang, M.; Zhao, J.; Zhou, J.; Chen, D. (Macromolecules, 2004)

(untitled) - Beltz, L. A.; Gustafson, R. R. (Carbon, 1996)

(untitled) - Pandey, G. C.; Kumar, A. (Polym. Test., 2002)

(untitled) - Tuinstra, F.; Koenig, J. L. (J. Chem. Phys., 1970)

(untitled) - Jawhari, T.; Roid, A.; Casado, J. (Carbon, 1995)

(untitled) - Shao, Y.; Zhou, L.; Bao, C.; Ma, J. (Carbon, 2015)

(untitled) - Fiedler, A. K.; Fitzer, E.; Rozploch, F. (Carbon, 1973)

(untitled) - Duman, O.; Tuncķ, S.; Polat, T. G.; Bozoğlan, B. K. (Carbohydr. Polym., 2016)

(untitled) - Liu, T.; Li, Y.; Du, Q.; Sun, J.; Jiao, Y.; Yang, G.; Wang, Z.; Xia, Y.; Zhang, W.; Wang, K. (Colloids Surf., B, 2012)

(untitled) - Zhang, L. Y.; Zhang, W.; Zhou, Z.; Li, C. M. (J. Colloid Interface Sci., 2016)

(untitled) - Wu, X.-L.; Shi, Y.; Zhong, S.; Lin, H.; Chen, J.-R. (Appl. Surf. Sci., 2016)

(untitled) - Asfaram, A.; Ghaedi, M.; Yousefi, F.; Dastkhoon, M. (Ultrason. Sonochem., 2016)

(untitled) - Asfaram, A.; Ghaedi, M.; Hajati, S.; Goudarzi, A. (Ultrason. Sonochem., 2016)